Comparative study of coelomocytes from Arbacia lixula and Lythechinus variegatus: Cell characterization and in vivo evidence of the physiological function of vibratile cells. Issue 110 (March 2021) - Queiroz, Vinicius; Muxel, Sandra M.; Inguglia, Luigi; Chiaramonte, Marco; Custódio, Márcio R.
Abstract: The knowledge on echinoderm coelomocytes has increased in recent years, but researchers still face a complex problem: how to obtain purified cells. Even flow cytometry being useful to address coelomocytes in suspension, the need for a method able to provide isolated cells is still noteworthy. Here, we use Imaging Flow Cytometry (IFC) to characterize the coelomocytes of two sea urchin species – Arbacia lixula and Lytechinus variegatus – and obtain gates to isolate cell populations. Then, we used these gates to study the physiological response of A. lixula coelomocytes during an induced immune challenge with Escherichia coli . An analysis of area and aspect ratio parameters of the flow cytometer allowed the identification of two main cell populations in the coelomic fluid: circular and elongated cells. A combination of this method with nucleus labeling using propidium iodide allowed the determination of gates containing isolated subpopulations of vibratile cells, red spherulocytes, and two phagocytes subpopulations in both species. We observed that during an induced bacterial immune challenge, A. lixula was able to modulate coelomocyte frequencies, increasing the phagocytes and decreasing red spherulocytes and vibratile cells. These results indicate that vibratile cells and red spherulocytes act by immobilizing and stoping bacterial growth, respectively, cooperating with phagocytes in the immune response. The use of IFC was fundamental not only to identify specific gates for the main coelomic subpopulations but also allowed the investigation on how echinoids modulate their physiological responses during immune challenges. Furthermore, we provide the first experimental evidence about the role of vibratile cells, corroborating its involvement with the immune system. Graphical abstract: Image 1 Highlights: – Imaging flow cytometry provided gates containing isolated sea urchin coelomocytes. – Vibratile cell percentage decreased 24 h after Escherichia coli immune challenge. – Phagocytes, red spherulocytes, and vibratile cells could be cooperating during immune challenges.